Isu Penggunaan Kalimah Allah Oleh Pihak Kristian: Analisis Menurut Hukum Islam - Meerangani, Khairul Azhar; Ramli, Rushdi (Jurnal Fiqh, 2016)
The issue of the word Allah has given rise to a prolonged debate in the Malaysian society, resulting in uneasiness especially among the Muslims and the Christians. This study aims to identify the background of the issue and its evaluation from the contemporary Islamic legal perspective. The analysis takes into account discussion by Muslim scholars with regard to the original usage of the word Allah by non- Muslims as well as the evaluation of its principles based on the current reality in Malaysia. The ban on its usage in any non-Muslim publication is meant to safeguard the interest of both parties in order to maintain harmony in the Malaysian society.